Agarwood (gaharu) research rekindled interest, stirs debate at the 40th International Symposium on Essential Oils - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2009)

(untitled)
Savigliano, Italy Sept 7-9. The MOSTI-funded research (Science Fund 02-0l-16-SF0005) headed by Prof Mashitah Mohd Yusoff rekindled tremendous interest and debate when presented by lead researcher and FIST's lecturer, Saiful Nizam Tajuddin.